Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China - Wu, Xiangjuan; Liu, Zhen; Chen, Yu; Wang, Beixin (Zootaxa, 2019)
The final stadium larva of Euphaea superba Kimmins, 1936 is described and illustrated based on a male and a female specimens collected in Zhejiang province, China. The larvae were associated with the adults by mtCOI gene sequence. The larva of E. superba is diagnosed from other described members of the genus by the gena having 2–4 spines on outer side, the movable hook about 1.6 time as long as median cleft and female with primary genitalia extending to the posterior margin of abdominal segment 10.